United States : Publication of Financial Sector Assessment Program Documentation; Detailed Assessment of Observance of Basel Core Principles for Effective Banking Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper presents Detailed Assessment of the United States's observance of Basel Core Principles for Effective Banking Supervision. The U.S. financial system is large and highly diversified. At the end-2007, total U.S. financial assets amounted to almost four and a half times the size of GDP. Of this, however, less than a one-fourth quarter of total financial assets were accounted for by traditional depository institutions. The crisis has radically changed the shape of the U.S. financial system in a short timeframe.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet